Resistance Reconceptualized - Leighteizer, Valda Kathleen (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2006)
In vernacular understandings or conversations about resistance as it occurs with students in public schools, it is frequently viewed as a negative action or set of behaviours to be changed or curtailed. This paper puts forward an argument that allows for the possibility of seeing moments of resistance as something to be recognized and celebrated with students. I do not suggest that resistance must always or only be viewed in this manner, but rather that it might be viewed thus, and thereby allow for multiple understandings of an action such as resistance. Beginning with my own hegemonic understanding of resistance as a necessarily bad/undesirable characteristic or behaviour, I then build on Foucault’s relational approach to understanding power (and its operations), leading then to a discussion of student engagement as also a relational process and one that has more than one possible form. By offering a possibility of understanding student engagement as a process that works both within and outside the structures that produce and maintain the White, middle class, heterosexual, abled, Christian, male child as the defacto subject of schooling, I build an argument that opens a more fluid conception of resistance than the necessarily negative action it is often perceived to be.